Climate change and the city: Building capacity for urban adaptation. (January 2015) - Carter, Jeremy G.; Cavan, Gina; Connelly, Angela; Guy, Simon; Handley, John; Kazmierczak, Aleksandra
Highlights: Cities and urban areas are facing a strong adaptation imperative. Spatial planning can support proactive cross-cutting urban adaptation. Adaptation would benefit from 'repositioning' to emphasise links to core urban agenda. Collaborative approaches are vital to meet the urban adaptation challenge. Abstract: The significant shifts in climate variables projected for the 21st century, coupled with the observed impacts of ongoing extreme weather and climate events, ensures that adaptation to climate change is set to remain a pressing issue for urban areas over the coming decades. This volume of Progress in Planning seeks to contribute to the widening debate about how the transformation of cities to respond to the changing climate is being understood, managed and achieved. We focus particularly on spatial planning, and building the capacity of this key mechanism for responding to the adaptation imperative in urban areas. The core focus is the outcomes of a collaborative research project, EcoCities, undertaken at the University of Manchester's School of Environment and Development. EcoCities drew upon inter-disciplinary research on climate science, environmental planning and urban design working within a socio-technical framework to investigate climate change hazards, vulnerabilities and adaptation responses in the conurbation of Greater Manchester, UK. Emerging transferable learning with potential relevance for adaptation planning in other cities and urban areas is drawn out to inform this rapidly emerging international agenda. Approaches to build adaptive capacity challenge traditional approaches to environmental and spatial planning, and the role of researchers in this process, raising questions over whether appropriate governance structures are in place to develop effective responses. The cross-cutting nature of the adaptation agenda exposes the silo based approaches that drive many organisations. The development of a collaborative, sociotechnical agenda is vital if we are to meet the climate change adaptation challenge in cities.